Flip-flash phonics: homonyms (Ideal School Supply, McGraw Hill Grand Rapids, Mich., 2002)
"Flip-Flash Phonics: Homonyms" is an engaging educational tool aimed at helping children grasp the concept of homonyms through a fun and interactive format. This book features colorful illustrations and activities that encourage young readers to explore words that sound the same but have different meanings. By using flip cards and playful examples, it enhances phonics skills while making learning enjoyable, making it a valuable resource for teachers and parents alike.